Robot-assisted radical cystectomy with intracorporeal heterotopic neocystis: a single-centre experience of complications - V. N. Pavlov; M. F. Urmantsev; M. R. Bakeev (Вестник урологии)
Introduction. Bladder cancer (BCa) ranks 10th among all diagnosed malignant tumours. To date, radical cystectomy (RCE) with pelvic lymphadenectomy is the gold standard for the treatment of aggressive forms of BCa. The development of minimally invasive technologies has contributed to the active introduction of robot-assisted interventions into surgical practise. RCE is a modern and relevant method for treating muscle-invasive BCa and high-risk non-muscle-invasive BCa. Over the past decade, many works have been accumulated that demonstrate the success of robot-assisted RCE with intracorporeal neocystis.Objective. To analyse the complications classified according to Clavien-Dindo after robot-assisted radical cystectomies with intracorporeal heterotopic neocystis based on a single centre.Materials & methods. From 2021 to 2022, a retrospective study was conducted based on Bashkir State Medical University Clinics aimed at studying complications after robot-assisted RCEs. The group investigated consisted of 200 male and female patients with an established diagnosis of BCa. All patients were shown surgical treatment in volume of RCE by Bricker with pelvic lymphadenectomy. Surgical intervention was performed using the DaVinci ® Si robot-assisted system. After 30 and 90 days, the complications that occurred and the ways to correct them were evaluated.Results. Only 35 patients (17.5%) had 30-day complications, which were grade I-III. Fourteen (7%) patients had 90-day complications having II and III degrees. Patients with grade III or II and III complications occurred during the first 30 days after surgical treatment subsequently had 90-day complications (p < 0.05). There were no statistically significant differences between the types of 30-day complications of II and III degree and the subsequent 90-day complications (p < 0.05).Conclusion. Robot-assisted RCE is an effective and technologically advanced method of treating patients with aggressive forms of BCa. Our study demonstrates low rates of surgical complications after this surgical intervention.